Synthesis of Al-containing MmNi5 by mechanical alloying: Milling stages, structure parameters and thermal annealing - Obregon, Sergio Alejandro (2012)
In this work, intermetallics of MmNi5-xAlx composition (Mm = mischmetal = La0.25Ce0.52Nd0.17Pr0.06) where x stands for 0.5 and 1 were synthesized by low energy reactive alloying. Minor structures present on the sample were identified. Structural parameters were calculated. Four stages of milling were characterized as a function of the integrated milling time (tim). The stages were characterized as Initial, Intermediate, Final and Completion.  Initial stage ranges from 0 to 20 h. Intermediate and Final from 20 to 50 h and from 50 to 120 h, respectively.  Completion stage occurs at (tim  > 120 h. From these results an optimum milling time range was estimated. Energy consumption experiments at laboratory scale were done to optimize annealing parameters and to compare this low energy mechanical alloying  and low temperature annealing method  with high temperature traditional ones [a,b] The optimization was correlated to the structural parameters obtained on the structure. From these results, an improvement on the milling time-annealing process was proposed.